2022
DOI: 10.21203/rs.3.rs-1315303/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Barriers and facilitators for population genetic screening in healthy populations: a systematic review

Abstract: Studies suggest that 1-3% of the general population in the United States unknowingly carry a genetic risk factor for a common hereditary disease. Knowing this information could help guide improved disease risk management and preventive care. Population-based genetic screening is the process of offering otherwise healthy patients screening for genetic variants that predispose them to certain diseases that are “clinically actionable”, meaning that they can be prevented or mitigated if they are detected early in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…This aligns with prior work that has demonstrated potential disparities in genetic services use among these populations. (Shen et al, 2022;Sanderson et al, 2004;Childers et al, 2018;Armstrong et al, 2005;Orlando et al, 2019; The National Academies Collection: Reports funded by National Institutes of Health, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This aligns with prior work that has demonstrated potential disparities in genetic services use among these populations. (Shen et al, 2022;Sanderson et al, 2004;Childers et al, 2018;Armstrong et al, 2005;Orlando et al, 2019; The National Academies Collection: Reports funded by National Institutes of Health, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies examining the public's interest in population genetic screening have shown that awareness about genetic screening for certain types of cancer is associated with being non-Hispanic White (Hay et al, 2018;Rubinsak et al, 2019), willingness to pay for testing, having a family history of cancer, and higher educational attainment. (Shen et al, 2022). Other population characteristics such as access to a primary care provider, rurality, income, insurance, sexual orientation, and gender have been shown to be related to genetic services use; however little is understood about their association with interested in and likelihood to participate in PGS.…”
Section: Introductionmentioning
confidence: 99%
“…We adhered to the Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) reporting guidelines ( Moher et al, 2009 ) for this review ( Supplementary Appendix SA ). Details of the protocol for this systematic review were registered on PROSPERO and can be accessed at https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42020198198 ( Shen et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Details of the protocol for this systematic review were registered on PROSPERO and can be accessed at https://www. crd.york.ac.uk/prospero/display_record.php?ID= CRD42020198198 (Shen et al, 2022).…”
Section: Protocol and Registrationmentioning
confidence: 99%
“…Despite the accessibility of genetic information and growth in population-based screening, challenges exist to scaling up these approaches, including engaging large multidisciplinary teams of researchers and clinicians, ensuring public understanding of genetic information, equitable access and participation of diverse populations in genetic screening, and sustainability of population-based genetic screening programs. 6,7 Synergistic efforts to optimally use genomic information to inform clinical care and improve population health requires the use of implementation science to assess engagement with learning health systems, de ne and monitor project outcomes, and re ne and evaluate processes for improvement.…”
Section: Introductionmentioning
confidence: 99%